Perceptions and utilization of generic medicines in Guatemala: a mixed-methods study with physicians and pharmacy staff. Issue 1 (December 2017) - Flood, David; Mathieu, Irène; Chary, Anita; García, Pablo; Rohloff, Peter
Abstract Background Access to low-cost essential generic medicines is a critical health policy goal in low-and-middle income countries (LMICs). Guatemala is an LMIC where there is both limited availability and affordability of these medications. However, attitudes of physicians and pharmacy staff regarding low-cost generics, especially generics for non-communicable diseases (NCDs), have not been fully explored in Guatemala. Methods Semi-structured interviews with 30 pharmacy staff and 12 physicians in several highland towns in Guatemala were conducted. Interview questions related to perceptions of low-cost generic medicines, prescription and dispensing practices of generics in the treatment of two NCDs, diabetes and hypertension, and opinions about the roles of pharmacy staff and physicians in selecting medicines for patients. Pharmacy staff were recruited from a random sample of pharmacies and physicians were recruited from a convenience sample. Interview data were analyzed using a thematic approach for qualitative data as well as basic quantitative statistics. Results Pharmacy staff and physicians expressed doubt as to the safety and efficacy of low-cost generic medicines in Guatemala. The low cost of generic medicines was often perceived as proof of their inferior quality. In the case of diabetes and hypertension, the decision to utilize a generic medicine was based on multiple factors including the patient's financial situation, consumer preference, and, to a large extent, physician recommendations. Conclusions Interventions to improve generic medication utilization in Guatemala must address the negative perceptions of physicians and pharmacy staff toward low-cost generics. Strengthening state capacity and transparency in the regulation and monitoring of the drug supply is a key goal of access-to-medicines advocacy in Guatemala.